Gut microbiota changes in airway diseases: a systematic review - Passos, Fabine Correia; Oliveira, Lucas Matheus Gonçalves de; Leal Neto, Odilon Lobão; Jesus, Fabíola Ramos; Falcão, Michelle Miranda Lopes; Neves, Margarida Célia Lima Costa; Lemos, Antônio Carlos Moreira; Baccan, Gyselle Chrystina (Revista de Ciências Médicas e Biológicas, 2020)
Introduction: studies have highlighted the importance of gut microbiota (GM) to the host immune defenses, influencing the host development and physiology. Changes in the composition and diversity of GM have been detected in some disease and could be implicated in the pathophysiological mechanisms of them. Objective: the purpose of this study was to show an overview of the current knowledge about the GM of patients with airway diseases (AD). Methodology: the literature search was performed in four databases, using a combination of the descriptors: “Gastrointestinal Microbiome”, “Gut Microbiome”, “Gut Microbiota”, “Cystic Fibrosis” (CF), “Asthma”, “Pulmonary Hypertension” (HP) and/or “Chronic Obstructive Pulmonary Disease” (COPD). Results: fifteen studies were herein included: ten of CF and five of asthma. No study about other AD matched the inclusion criteria. In all studies about CF, changes were detected in GM, particularly quantitative and qualitative microbial changes. For asthma, data showed changes in GM also including a reduction of microbial richness, evenness and diversity and in the Bacteroidetes/Firmicutes ratio. Conclusions: the current data indicate the existence of GM changes in AD. However, due to the few studies for asthma and the lack of investigations on HP and COPD, it was not possible to confirm whether these GM changes are observed in other AD. Furthermore, this review shows the necessity of more studies in this area to characterize dysbiosis and which alterations are more frequent observed in AD patients.